PEMBERDAYAAN SUKU DAYAK PEDALAMAN MELALUI INOVASI PERTANIAN, EKONOMI, PENDIDIKAN DAN KESEHATAN TERPADU UNTUK MEWUJUDKAN MASYARAKAT SEHAT, CERDAS, DAN SEJAHTERA DI DAERAH TERTINGGAL KALIMANTAN BARAT - Eko Sarwono; Selviana Selviana; Ismail Saleh (Jurnal Buletin Al-Ribaath, 2017)
The majority of indigenous Dayak farmers in Toho district encounter several issues. Their productivity was varied seasonally. In the rainy season, they were difficult to dry paddy in the sun. They also required costly diesel to fuel their threshing machines. In the health area, this region ever promulgated to set up Desa Siaga, but until now the discourse has not been realized. Health coverages such as childbirth by medical labor, exclusive breastfeeding, PHBS, and environmental sanitation were extremely low. This programs empowered dayak farmer community through Innovations in Agriculture, Economics, Education and Health Integrated (PERENDIKESDU). The programs included (a) Increasing the entrepreneurial agricultural economics, methods/concept used to overcome the problems, namely: the establishment and coaching a group of women farmers, training of making rice with simple biomass drying machine and simple threshing machine, training nursery plantation processing, packaging socialization plantation products. (b) Establishment and Development of alert village, methods which are used to treat the problems namely: workshops, health promotion include counseling on health behavior, socialization healthy latrines, clean water supply, sanitation, training of village cadres standby and Posyandu cadres, management training standby village, ground socialization land use for medicinal plant families (toga). (c) Elimination of illiteracy, methods which are used to treat the problems, namely: the implementation of training for creating collages, mosaics, and a montage of simple materials, realization Morance training methods, training of cadres illiteracy, the establishment of home building illiteracy. Keywords: Agriculture, Economics, Education, Health, PERENDIKESDU, Dayak.The majority of indigenous Dayak farmers in Toho district encounter several issues. Their productivity was varied seasonally. In the rainy season, they were difficult to dry paddy in the sun. They also required costly diesel to fuel their threshing machines. In the health area, this region ever promulgated to set up Desa Siaga, but until now the discourse has not been realized. Health coverages such as childbirth by medical labor, exclusive breastfeeding, PHBS, and environmental sanitation were extremely low. This programs empowered dayak farmer community through Innovations in Agriculture, Economics, Education and Health Integrated (PERENDIKESDU). The programs included (a) Increasing the entrepreneurial agricultural economics, methods/concept used to overcome the problems, namely: the establishment and coaching a group of women farmers, training of making rice with simple biomass drying machine and simple threshing machine, training nursery plantation processing, packaging socialization plantation products. (b) Establishment and Development of alert village, methods which are used to treat the problems namely: workshops, health promotion include counseling on health behavior, socialization healthy latrines, clean water supply, sanitation, training of village cadres standby and Posyandu cadres, management training standby village, ground socialization land use for medicinal plant families (toga). (c) Elimination of illiteracy, methods which are used to treat the problems, namely: the implementation of training for creating collages, mosaics, and a montage of simple materials, realization Morance training methods, training of cadres illiteracy, the establishment of home building illiteracy. Keywords: Agriculture, Economics, Education, Health, PERENDIKESDU, Dayak.